Tumbalik - Reglos, Precious Tolentino 1991-; University of the Philippines. College of Mass Communication (2014)
"Marriage is the state of being united to a person in a consensual and contractual relationship. It is a promise and a commitment that should be bounded by virtues and love. Tumbalik is about a woman who is a mother and a wife, in a troubled relationship struggling to maker her marriage work. Making her daughter aware of the situation between her and her father, she finds out her daughter is newly engaged. Letting go and moving on from people who take you for granted that you love is a process infused with pain and hatred that one must fight to overcome. Acceptance is always a start for a change to happen."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman
Keywords: Marriage; Family relationships